Biological and ecological classification of biomimicry from a biology push standpoint. Issue 11 (22nd November 2019) - Bae, Haejin; Lee, Eunok
Abstract: Biomimicry refers to a cooperative process that develops a sustainable world by taking inspiration from the structure, function, process, and mechanism of an organism adapted to the environment through the evolution of nature. A classification system of biomimicry from a biological and ecological point of view (biology push) can provide a framework for the sustainable development of society, the environment, and the economy. Thus, the purpose of this study was to categorize biological and ecological functions and to present a collaborative biomimicry system that suggests engineering and industrial sectors where biomimicry functions can be applied. Based on biology push, the biological and ecological functions were divided into six groups with subgroups of specific features, related to the fields of technology and industry. Through the formulation of the new biological functional framework, the biomimicry system can be used as a simple classification tool to determine the expected value of the final product as well as provide the knowledge data required in engineering and industry.